South Arabia's prehistoric monument landscape shows social resilience to climate change. - Joy McCorriston; Lawrence Ball; Michael J Harrower; Ian M Hamilton; Sarah J Ivory; Matthew J Senn; Tara Steimer-Herbet; Abigail F Buffington; Ali Ahmad Al-Kathiri; Ali Musalam Al-Mahri (PLoS ONE)
In arid regions across northern Africa, Asia and Arabia, ancient pastoralists constructed small-scale stone monuments of varying form, construction, placement, age, and function. Classification studies of each type have inhibited a broader model of their collective and enduring role within desert socio-ecosystems. Our multivariate analysis of 371 archaeological monuments in the arid Dhofar region of Oman identifies environmental and cultural factors that influenced variable placement and construction across a 7000-year history. Our results show that earlier monuments were built by larger, concurrent groups during the Holocene Humid Period (10,000-6000 cal BP). With increasing aridification, smaller groups constructed monuments and eventually switched to building them in repetitive visits. Our model emphasizes the core role of monuments as a flexible technology in social resilience among desert pastoralists.